Exosome Mimetics-Loaded Hydrogel Accelerates Wound Repair by Transferring Functional Mitochondrial Proteins - Jie Zhu (Frontiers in Bioengineering and Biotechnology, 2022)
Loading human umbilical mesenchymal stem cell (hUMSC) derived exosomes onto hydrogel scaffolds is a strategy for rapid wound healing. The clinical application of exosomes is hindered by low production, and exosome mimetics could be substituted for exosomes. Here, the therapeutic effects of exosome-loaded hydrogels and exosome mimetic-loaded hydrogels on wounds are evaluated. Our results revealed that exosome mimetic-loaded hydrogels promote wound healing more efficiently than exosome-loaded hydrogels. Exosome mimetics can promote the proliferation and migration of dermal fibroblasts (hDF-a) cells in vitro. To investigate how exosome mimetics play a role, proteomics analysis was applied, and the obtained results suggested that exosome mimetics significantly enrich mitochondrial-derived oxidative phosphorylation-related proteins in comparison to exosomes. Overall, our work envisages the emerging potential of exosome mimetics, which take the advantage of exosomes and can be promising candidates for exosomes. It also suggests that hUMSC-derived exosome mimetic-loaded hydrogels have remarkable prospects for clinical application.